Pengaruh Credibility, Information Quality dan Content Quality pada Konten Affiliate Marketing di Tiktok terhadap Purchase Decision Generasi Z - Bella Aulia; Nadya Fadillah Fidhyallah; Rizka Zakiah (Indo Publishing, 2026)
This study aims to analyze the effect of Credibility (X1), Information Quality (X2), and Content Quality (X3) in TikTok affiliate marketing content on Generation Z's Purchase Decision (Y). The research is motivated by a gap between theoretical expectations and actual consumer behavior, where consumers make purchases despite perceiving the affiliate's message quality as low. Using a quantitative approach with a cross-sectional design, data was collected via online questionnaires from 150 Gen Z respondents in DKI Jakarta. The sample was selected using purposive sampling, requiring respondents to have viewed affiliate content and purchased via TikTok Shop. Data analysis was conducted using multiple linear regression via SPSS. The results reveal that Credibility has a positive but insignificant effect on Purchase Decision (H1 rejected). Conversely, Information Quality and Content Quality have a positive and significant effect, with Content Quality being the most dominant factor. Simultaneously, these variables explain 73.8% of the purchase decision variance (Adjusted R² = 0.738). These findings indicate that Gen Z's purchase decisions are driven more by product information clarity and attractive content packaging than mere trust in the affiliate's honesty. Consequently, brands and affiliates must prioritize investing in information and content quality for TikTok affiliate marketing strategies.